Key Theory and Philosophy of Mind (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2006)
This article initially reflects on the beginnings of the close association between the author and Danie Strauss, whose work is the theme of this festschrift. The impact of the mentioned association, together with later philosophical influences, contributed to the author’s work on “discourse archaeology”. The article then takes up a particular tool of this archaeology, key theory, and explains its relevance for philosophy of mind.